Resonant inductive wireless power transfer system for wireless capsule endoscopy application / Md. Rubel Basar - Md. Rubel , Basar (2017)
Resonant inductive wireless power transfer (WPT) system is regarded as a promising way to overcome high power demand for future wireless capsule endoscopy (WCE). Despite much attentions in this area, aspects such as overall power transfer efficiency (PTE) and received power stability (RPS) remain suboptimal and therefore investigation for further improvement is still required. Thus, this thesis presents several techniques to improve the PTE and RPS of WPT system for WCE application. In order to improve the PTE and RPS, three new power transmission coils (PTCs) are proposed which are named as PTC-I, PTC-II, and PTC-III. The proposed PTCs are mainly differed by the number of coil segments used, separation and number of turn ratio among the coil segments. The design parameters of proposed PTCs have been rigorously analyzed with complete mathematical models and computer simulations. The improvement in the power receiving side is contributed by the optimization of number of strands in the power receiving coil (PRC), incorporation of high permeability ferrite core, mixed resonance scheme, and power combining technique with 2-3 D PRC. For the overall inductive link, a multi-coils link approach is analyzed in WCE platform and an optimized 3-coils link is proposed to minimize effect of load resistance to the PRC. Finally, the PTC is designed in wearable form for compact portable WPT system. The results of analysis and experimental test indicate a remarkable improvement of PTE and RPS. The PTE obtained by the proposed optimal design is 8.12% when 758 mW of power being transferred. This PTE is remarkably higher than the PTE of 3.55% obtained by the best existing design in literature. The optimum proposed design also attained overall RPS of 79.2% whereas only 33.9% of RPS obtained by the best existing design. In addition, an electromagnetic effect analysis is performed with incorporation of PRC and high permeability ferrite core in a multi-layer homogenous body model. Results from this analysis indicate that 200 mW power can be transferred safely based on the guidelines provided by the ICNIRP.